Math, asked by naincyraj24, 3 months ago

prove that (a+b+c) ³-a³-b³-c³=(a+b)(b+c) (c+a)​

Answers

Answered by llElegantlavenderll
17

Answer:

(a+b+c)³-a³-b³-c³

=(a+b)³+3(a+b)²c+3(a+b)c²+c³-a³-b³-c³

=a³+3a²b+3ab²+b³+3(a²+2ab+b²)c+3ac²+3bc²+c³-a³-b³-c³

=3a²b+3ab²+3a²c+6abc+3b²c+3ac²+3bc²

=3(2abc+a²b+ab²+a²c+ac²+b²c+bc²)

3(a+b)(b+c)(c+a)

=3(ab+b²+ac+bc)(c+a)

=3(abc+b²c+ac²+bc²+a²b+ab²+a²c+abc)

=3(2abc+a²b+ab²+a²c+ac²+b²c+bc²)

LHS=RHS

Answered by raman121977
2

Answer:

Question wrong ha

Step-by-step explanation:

3(a+b)(b+c) (c+a) ho ga

Similar questions